Fishery Hub: E-Commerce Produk Perikanan Berbasis Website Untuk Mendukung Ekonomi Biru Berkelanjutan - Maskur Faris Ardani; Ma'ruf Efendi; Syifa Fajar Maulani (Lambda: Jurnal Ilmiah Pendidikan MIPA dan Aplikasinya, 2026)
Fish distribution in Indonesia still faces challenges such as lengthy marketing chains, low utilization of cold-storage facilities, and limited market access for small-scale fishers, as reflected in conditions in Lampung Province. This study develops Fishery Hub, a website-based e-commerce platform connecting fishers, processed-fish MSMEs, and consumers within a single digital ecosystem to support a sustainable blue economy. The research applies a Research and Development (R&D) method with a User-Centered Design (UCD) approach, covering problem identification, system design using Unified Modeling Language (UML), implementation on the Laravel framework, integration with the Tripay payment gateway and the Kiat Ananda shipping API, and feasibility testing using the System Usability Scale (SUS) and User Acceptance Test (UAT) involving 20 respondents (fishers, MSME actors, and consumers). Results show an average SUS score of 99.375 (excellent category) and a UAT acceptance rate of 100% (highly accepted category), indicating that Fishery Hub is easy to use and its main features are relevant to user needs. The platform has the potential to shorten distribution chains, increase information transparency, and empower local fishery businesses, supporting Indonesia's sustainable blue economy vision.